Analysis of the Spread of Covid-19 Worldwide: Difference and Similarity - JOSSOU, Thierry Rock; MEDENOU, DATON (My University, 2022)
Background: Today, the world faces a global health challenge caused by COVID-19, but its lethal effect varies from one country to another. Indeed, the COVID-19 does not seem to have the same gravity and lethality wherever transmission focus and chains exist. With COVID-19 epidemic’s progression, measures to stem its propagation are more and more drastic and numerous. Some were taken in a hurry; others are the result of feedback. Did the multiple measures taken to fight the coronavirus have to be adapted to the local specific conditions of each country? In this work, a review of measures taken to stop this pandemic propagation will be first proposed as well as their impacts analysis. It will also provide an overview of COVID-19 levels of vulnerability depending on the disposals and measures taken to fight this virus which differs from one country to another and sometimes overlap. In a second step, we will relate the disparities’ reasons of the lethality rate which must be interpreted with precaution, based on the 10,000 people scale’s demographic rate considered to be reasonable far from any overbidding or chaotic overestimation. The scenarios studied keep into account a wide range of standards and measures adopted, such as: health system’s condition (medical infrastructure, joblessness allowance, etc.), socio-economic development, epidemics’ propagation mode (confinement, age, population density, etc.) and in particular reactivity in measures’ taking (borders’ closing, a mask taking and wearing obligation, distancing, etc.). The choice of France as a reference to compare the different cases is not harmless since it allows comparisons with countries of the same rank at the economic, demographic, social and geographic level, and also with other countries presenting different socio-economic and demographic situations. Result: The analysis of the various scenarios implemented to combat the spread of the coronavirus and cautious answers’ research forces us to ask the following questions: did we need to distribute given statistics between deaths due to coronavirus or death with coronavirus? Then how can we distinguish between the true death due to coronavirus and its accidental presence at the death time? These questions and observations brought out that, the available statistics are relatively incomplete or even inconsistent and don’t allow rational explanation. Conclusion: COVID-19 advent and its globalization recommend courage, clarity and humility. In addition to the uncertainty and ambiguity of incomplete or distorted data, their using modality would be at the origin of bad decisions. The design of efficient pandemic scenarios combined with a logical outcome processing structure establishment can mitigate the risk of incomplete data. Today, epidemiological statistics, moreover, informative and indicative can be at coming up crises’ better treatment origin. The right strategy and the right decision-making can restore the society liveliness in these troubled times. We can say that it is in the announced results there is lacking, creating a psychosis through fear and dramatization.
Keywords: COVID-19; Confinement; Statistics; Coronavirus; Health; Management